Histórias de mulheres cuidadas por práticas integrativas e complementares: um estudo etnográfico - Saraiva, Alynne Mendonça (2015)
Socioeconomic and cultural changes of society engineered in recent decades a culture of individualism and exclusion. These changes mainly affect women, causing them to helplessness, low self-esteem and loneliness. Such feelings are often embodied in the form of pain or disease. As a consequence of these social aggressions, women come seeking therapeutic resources that can respond to their physical, psychological and spiritual needs. Integrative and complementary practices bring this proposal for integral care and are being increasingly sought after by women. In this sense, the aim in this work was: analyzing stories of women who sought integrative and complementary practices. The study followed the precepts of Resolution 466/12, being approved by the Research Ethics Committee under CAAE: 39806114.0.0000.5188. This research was conducted according to a benchmark according to the anthropological and ethnographic method. For collection and production of the empirical material, there was used the technique of Oral History of life with 8 women users of the Center for Integrative and Complementary Practices, in the municipality of João Pessoa/PB. The analysis and interpretation of the material were made on the basis of units of meaning (themes) more evident and constants in the narratives and the vital tone of each story. Thus, the following categories have been developed: a) sources and manifestations of female suffering, b) therapeutic itineraries and rituals of care for women and c) reconstruction of identity and otherness: paths for the female protagonism. In the stories reported, it was observed that women have sought care, because they reported sadness, low self-esteem, loneliness, fatigue, pain, helplessness, anxiety and insecurity. These complaints were associated with the sufferings experienced in respect of affective loss, workload of care, migration, interruption of life projects, and family disputes. The paths in search for care were influenced mainly by the socio-cultural context of each contributor, so that many of them resorted primarily to biomedical services. While not all employees had been through these services before resorting to integrative and complementary practices, they showed differences between the approach of allopathic medicine and the PICs, especially with regard to the applied therapy, to the professional-user relationship and the belief in the therapeutic efficacy. Care through integrative and complementary practices provided to these women greater autonomy; favored the construction of bounds; the rescue of self-esteem; promoted the empowerment and took them to reassure their lives and their stories.